Peningkatan Karakteristik Aspal Menggunakan Bahan Tambah Nano Fly Ash - Mulyawati, Firda Jelita; Hanifah, Witri Siti; Syafier, Siegfried (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2024)
Asphalt is a primary component in road pavement construction. Optimizing the utilization of industrial waste, such as fly ash from coal-fired power plants, is increasingly important as the number of companies using coal as fuel continues to grow. Although fly ash is widely used, applying nano fly ash as an asphalt additive remains limited. This study aims to evaluate the effectiveness of nano fly ash as an additive to improve the characteristics of asphalt. The research follows an experimental method conducted entirely in a laboratory setting. Testing was based on the 2018 Bina Marga Technical Specifications, with procedures aligned to AASHTO, ASTM, and SNI standards to ensure accurate and reliable results. Nano fly ash was added to Pen 60/70 asphalt in variations of 0%, 1%, 2%, and 2.5%. Each asphalt sample underwent parameter tests, including stability, flow, density, and stiffness. Results showed that the 1% addition provided the best outcomes, meeting all specified standards and demonstrating improved asphalt characteristics across multiple parameters. Variations of 2% and 2.5% yielded fewer compliant parameters, suggesting diminishing returns at higher nano fly ash levels. These findings indicate that nano fly ash can be a viable additive for Pen 60/70 asphalt, with a recommended optimal use of 1%. Further studies on economic viability and scalability are suggested to enhance the practical application of this material. Keywords— Pen 60/70 Asphalt, Nano Fly Ash Additive, Road Pavement Improvement, Industrial Waste Utilization